Transcranial Magnetic Stimulation for Improving Dysphagia After Stroke: A Meta-Analysis of Randomized Controlled Trials - Yu-lei Xie; Yu-lei Xie; Shan Wang; Shan Wang; Shan Wang; Jia-meng Jia; Jia-meng Jia; Yu-han Xie; Xin Chen; Xin Chen; Wu Qing; Wu Qing; et al. (Frontiers in Neuroscience, 2022)
BackgroundRehabilitation of post-stroke dysphagia is an urgent clinical problem, and repetitive transcranial magnetic stimulation (rTMS) has been widely used in the study of post-stroke function. However, there is no reliable evidence-based medicine to support the effect of rTMS on post-stroke dysphagia. This review aims to evaluate the effectiveness and safety of rTMS on post-stroke dysphagia.MethodsEnglish-language literature published before December 20, 2021, were searched in six electronic databases. Identified articles were screened, data were extracted, and the methodological quality of included trials was assessed. Meta-analysis was performed using RevMan 5.3 software. The GRADE method was used to assess the quality of the evidence.ResultsA total of 10 studies with 246 patients were included. Meta-analysis showed that rTMS significantly improved overall swallowing function (standardized mean difference [SMD]−0.76, 95% confidence interval (CI)−1.07 to−0.46, p < 0.0001, n = 206; moderate-quality evidence), Penetration Aspiration Scale (PAS) (mean difference [MD]−1.03, 95% CI−1.51 to−0.55, p < 0.0001, n = 161; low-quality evidence) and Barthel index scale (BI) (MD 23.86, 95% CI 12.73 to 34.99, p < 0.0001, n = 136; moderate-quality evidence). Subgroup analyses revealed that (1) rTMS targeting the affected hemisphere and targeting both hemispheres significantly enhanced overall swallowing function and reduced aspiration. (2) Low-frequency rTMS significantly enhanced overall swallowing function and reduced aspiration, and there was no significant difference between high-frequency rTMS and control group in reducing aspiration (p = 0.09). (3) There was no statistical difference in the dropout rate (low-quality evidence) and adverse effects (moderate-quality evidence) between the rTMS group and the control group.ConclusionrTMS improved overall swallowing function and activity of daily living ability and reduced aspiration in post-stroke patients with good acceptability and mild adverse effects.